Triamcinolone Acetonide Injection and Topical as an Alternative Method for Mucocel Therapy - Ronal, Ahmad; Azzahra, Fathimah; Surachmin, Audiawati; Nurfianti (YARSI Dental Journal, 2024)
Introduction: Mucocele is a swelling caused by the collection of saliva from the ducts of minor salivary glands that are cut off or blocked. This is a salivary gland cyst that contains mucus and generally founded in the oral cavity. Surgery is the most popular therapy in the treatment of mucocele. There are various alternative therapeutic modalities that can be used including laser ablation, cryosurgery, sclerotherapy, micromarsupialization, laser surgery, injection of sclerosis agents, and corticosteroid injection. Case and management: This paper describes the treatment of mucoceles using triamcinolone acetonide that is quite often used in the oral cavity. The therapy carried out is intradermal injection of 0.2 ml of triamcinolone acetonide IA/ID (10 mg/ml) and topical application of triamcinolone acetonide ointment in orabase 0.1% 6x/day. One week later it was seen that the mucocele lesion had almost disappeared. Discussion: Corticosteroids act as potent anti-inflammatory agents and also act like sclerosing agents causing shrinkage of the dilated salivary ducts. Conclusion: Triamcinolone acetonide can be an alternative therapy besides surgery in the management of mucocele cases. The application can be done by intradermal injection and topical ointment. No side effects were found at the end of treatment.